A comparison of digital morphometry and clinical measurements of ears. Issue 4 (September 2013) - Öberg, Martin; Svensson, Henry; Björk, Christoffer; Flodin, Johan; Wikström, Sven Olof
Abstract Clinical measurements are necessary in many routine follow-ups and scientific evaluations, but the accuracy of these measurements is seldom challenged. The size of the reconstructed ear is one important parameter in the follow-up regarding patients operated on due to microtia. With the introduction of digital morphometry one was obliged to evaluate its accuracy in comparison to its analogue equivalents. In a first series of measurements the ears of 30 persons were assessed using digital morphometry, compass and ruler, and calliper to test the accuracy of these methods. In a second series of measurements, 10 patients with reconstructed unilateral microtia were assessed with digital morphometry to test the inter-individual variation of this method. The accuracy of digital morphometry was of the same magnitude as the manual methods. When the inter-individual variation of accuracy was assessed in digital morphometry it was found that random error differed from person to person. In scientific settings, for instance when evaluating possible growth of the cartilage framework, the specific individual accuracy must therefore be taken into account in order to draw safe conclusions.